Development and Validation of a Motion Graphic Animation Video on Cyberbullying for Grade VII Informatics Using 4D Model - Muhammad Teguh Hidayatullah; Zelhendri Zen; Ulfia Rahmi; Mutiara Felicita Amsal (Indonesian Technology and Education Journal, 2026)
This study aims to develop a motion graphic animation learning video on Digital Bullying (Cyberbullying) material for Grade VII Informatics at SMP Negeri 29 Padang using the 4D development model (Define, Design, Develop, Disseminate), addressing the scarcity of effective learning media for this topic in junior high school Informatics. Data were collected through expert validation questionnaires, student practicality questionnaires, and pretest-posttest instruments, with 32 students participating in practicality testing and 22 students in effectiveness testing. Findings: The validity results showed a percentage of 98.00% (Very Valid) for both material and media aspects. The practicality test yielded an average score of 4.48 (89.55%), categorized as Very Practical. The effectiveness test using N-Gain Score produced a mean of 0.733 (73.34%), indicating a High improvement category. These findings confirm that the developed motion graphic animation learning video is valid, practical, and effective for Grade VII Informatics learning. The study demonstrates that AI-assisted production tools (Google Labs Flow/Veo 3, Google AI Studio, CapCut) can produce pedagogically valid and practically effective instructional animation, providing a replicable development model for resource-constrained Indonesian schools. Qualitative field observations suggest the media may also support affective development, including student empathy toward cyberbullying victims, an area not formally measured in this study but warranting future validated assessment. This study provides transparent documentation of an AI-assisted motion graphic production and iterative expert validation process within the Merdeka Curriculum framework, an approach not previously reported in the Indonesian Informatics education literature.